2013
DOI: 10.1371/journal.pone.0062653
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Infection Is Associated with the Development of Erythema Nodosum and Nodular Vasculitis

Abstract: Background Mycobacterium tuberculosis (MTB) infection has been suggested to contribute to the pathogenesis of erythema nodosum (EN) and nodular vasculitis (NV), the classic forms of panniculitis. However, there is little evidence to demonstrate the presence of MTB in the skin lesions. This study is aimed at evaluating the association between MTB infection and the development of EN and NV in a Chinese population.MethodsA total of 107 patients (36 EN, 27 NV, and 44 others) with vasculitis and 40 control cases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…The histopathologic analysis of the nodular lesion showed a panicullitis typical of Erythema nodosum and in one case neutrophilia inflammatory infiltrate and granulomas with caseous necrosis were detected. Similar to other cases previously reported of Erythema nodosum in patients with tuberculosis, fast acid bacillus were not detected [24,25] and the culture for M. tuberculosis was negative in both patients.…”
Section: Discussionsupporting
confidence: 88%
“…The histopathologic analysis of the nodular lesion showed a panicullitis typical of Erythema nodosum and in one case neutrophilia inflammatory infiltrate and granulomas with caseous necrosis were detected. Similar to other cases previously reported of Erythema nodosum in patients with tuberculosis, fast acid bacillus were not detected [24,25] and the culture for M. tuberculosis was negative in both patients.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that acute infection is associated with a systemic innate inflammatory response that precedes the induction of a detectable adaptive immune response. Erythema nodosum is still a symptomatic trigger that may lead to investigation and diagnosis of human infection with M. tuberculosis (4)(5)(6) or Mycobacterium bovis (7).…”
Section: Primary Response To M Tuberculosis Infectionmentioning
confidence: 99%
“…Erythema nodosum may also occur in drug-associated hypersensitivity reactions and malign disorders, but in our case, there was no drug that the patient had used and her tumor marker tests were normal. Erythema nodosum rarely occurs in adults with a tuberculosis infection (6). In 2012, Öz et al (7) conducted a 5-year retrospective epidemiologic study and found the rate of tuberculosis-associated erythema nodosum to be 3%.…”
Section: Discussionmentioning
confidence: 99%